Educação de jovens e adultos : palavras de mulheres a respeito do processo de escolarização. - Manzato, Carolina Rodrigues (2007)
The study approached some women s reintegration to the school environment, students from the Municipal Program of Youngsters and Adults Education in São José do Rio Preto, with the aim of understanding their reasons and objectives in the process. In order to do so, the following goals were established: comprehending their first school experiences to identify the factors responsible for the interruption (or privation) of their learning process, and the implications of these factors in the women s comming back to school; understanding the reasons why women with little or no education look for the school environment; identifying the kinds of learning offered by the school and investigating if they had implications in these women s practical lives; discovering if the women are satisfied (in case their lives have been changed by the learning process) and if they noticed the changes or not. This research s main questions: the education of youngsters and adults EJA, initial reading instructions and critical education, and the role destined to women throughout history, were accompanied by theoretical support of authors such as Paulo Freire, Sérgio Haddad, Maria Clara Di Pierro, Ana Maria Freire, Henry Giroux, Cláudia Viana, Joan Scot, among others. Data collection was carried out by means of semi-structured interviews with six learners, 41-58 years old. Data analysis was based upon Paulo Freire s theory, including the categories of oppression, marginalization, conscientiousness, autonomy, among others. We can previously and primarily stand out these women s courage, they still fight to restore rights that have been historically taken from them.